Extending the Transformative Potential of Mindfulness Through Team Mindfulness Training, Integrating Individual With Collective Mindfulness, in a High-Stress Military Setting - Tobias Mortlock, Jutta; Carter, Alison; Querstret, Dawn (Frontiers in Psychology, 2022)
Mindfulness has come to be considered an important approach to help individuals cultivate transformative capacity to free themselves from stress and suffering. However, the transformative potential of mindfulness extends beyond individual stress management. This study contributes to a broadening of the scope of contemplative science by integrating the prominent, individually focused mindfulness meditation literature with collective mindfulness scholarship. In so doing, it aims to illuminate an important context in which mindfulness interventions are increasingly prominent: workplaces, arguing that the specific intended effect of workplace mindfulness training is to help workers manage stress better. Since mindfulness in organizations impacts individual and collective processes, the study blends the above literatures to create a cross-level “next-generation” Team Mindfulness Training (TMT) pilot. Its potential in helping individuals and teams manage work stress better is investigated both individually and collectively, via a two-phase mixed-methods research study in two high-stress military work populations, and compared to a conventional (“first-generation”) 8-week mindfulness meditation program based on mindfulness-based stress reduction (MBSR). Results suggest that compared to the “first-generation” mindfulness program, TMT seems no less effective in raising individual stress management skills, and may hold more promise in generating collective capacity to manage stress and unexpected difficulty, linked to an apparent interdependence between collective and individual mindfulness capacity development. Based on these empirical results, the study contributes to theory in three important ways: First, it outlines how individual and collective mindfulness in workplaces are interdependent. Second, it explains why “next-generation” workplace training interventions should apply a cross-level approach. And third, it illustrates how moving beyond an inward-looking meditation focus in mindfulness training extends its transformative potential for people at work, individually as well as collectively. The study contributes to practice by providing a detailed outline of the pilot TMT program, offering a series of follow-up research opportunities to inspire further scientific innovation in workplace mindfulness training, especially for high-stress work populations. The study’s ultimate aim is to prompt a shift away from adapting clinically oriented, self-focused “first-generation” mindfulness training protocols, and towards a more prosocially oriented mindfulness science intent on generating wisdom and compassion, for one and all.